Information technologies in physical education of students. - Ivchatova T.V (Kharkov National Pedagogical University, 2011)
In the article is presented the systematized information about the using features of modern information technologies in practice of student physical education in not athletic universities. The analysis of domestic and foreign literature is conducted, and also Internet sources related to the problem of healthy way of life of students, and also to forming of active position in maintenance and strengthening of the health.